2019
DOI: 10.31160/jotci201927a201822
|View full text |Cite
|
Sign up to set email alerts
|

Successful treatment of lesions of multiple vessels with anomalous origin from the left coronary artery

Abstract: Anomalous coronary arteries are rare. The origin of the left main coronary artery from the right sinus of Valsalva is related to some events, such as syncope, arrhythmias, angina, among others. By and large, its diagnosis is incidentally made by coronary angiography. The presence of this type of anomaly may hinder percutaneous approach of the coronary lesions. The authors describe a case of left main coronary artery originating from the right sinus of Valsalva, associated to disease of multiple vessels. After … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…12 Another publication from our service, by Fernandes et al, described the successful percutaneous treatment of a clinical case with anomalous origin from the left main coronary artery in the right Valsalva sinus, with a course anterior to the pulmonary trunk and bifurcating into an anterior descending branch, at the level of the interventricular septum, with a 90% lesion in the bifurcation. 11 A third study, conducted by Araújo et al, described a rare case of anomalous origin of the right coronary artery, from the pulmonary artery with conservative treatment. 13 At the time, this case report and recent studies demonstrated percutaneous treatment of coronary anomalies with stent implantation is a safe option for selected patients, taking into account the clinical presentation, anatomy study, and training of the cath lab team.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…12 Another publication from our service, by Fernandes et al, described the successful percutaneous treatment of a clinical case with anomalous origin from the left main coronary artery in the right Valsalva sinus, with a course anterior to the pulmonary trunk and bifurcating into an anterior descending branch, at the level of the interventricular septum, with a 90% lesion in the bifurcation. 11 A third study, conducted by Araújo et al, described a rare case of anomalous origin of the right coronary artery, from the pulmonary artery with conservative treatment. 13 At the time, this case report and recent studies demonstrated percutaneous treatment of coronary anomalies with stent implantation is a safe option for selected patients, taking into account the clinical presentation, anatomy study, and training of the cath lab team.…”
mentioning
confidence: 99%
“…Therefore, it was important to analyze the anatomy of the coronary circulation and determine, in a more effective manner, the relation between the coronary artery and the other mediastinal structures. 10,11 Although current guidelines indicate revascularization surgery for an anomalous origin with a course between the aorta and the pulmonary artery as the treatment of choice, as reported in a multidisciplinary discussion with the Heart Team, an anatomical analysis of the patient was performed and the technical experience of the cath lab team was taken into account, and a percutaneous approach was performed, with success.…”
mentioning
confidence: 99%